An Unusual Presentation of a Complicated Appendicitis ‘’A Diagnostic Dilemma” and Role of Minimal Access Surgery - Makhandule, Fumani Charles; Bhuiyan, M. M. Z. U (British Journal of Healthcare and Medical Research, 2026)
Acute Appendicitis takes a classical clinical course of migratory periumbilical pain to the right iliac fossa. However, when the usual presentation takes a different course, it is difficult to face a diagnostic dilemma. A 17-year-old male patient presented with an acute abdomen from a dubious cause. There was a history of migratory periumbilical pain, radiating to the right upper quadrant. Maximal tenderness was found on the right upper quadrant. Pneumoperitoneum was shown on the Chest x-ray. After initial resuscitation, diagnostic laparoscopy was performed. Ascending retrocecal appendix was identified and tip of the appendix was ruptured on the right hypochondrium. Appendectomy performed followed by an antibiotic course. Post-operative period was complicated by abdominal collections for which relook laparoscopy performed, and pus was suctioned. Patient recovered well. Histology confirmed suppurative appendicitis. Laparoscopy is safe and feasible as diagnostic and therapeutic options in the acute abdomen when faced with a diagnostic dilemma.